GROWTH AND YIELD OF ONION (Allium Cepa fa.ascolanicum) PHILIPINES VARIETY ON APPLICATIONS MYCORRHIZAL AND ORGANIC FERTILIZER IN THE LAND POST MERAPI ERUPTION - Suprapto Suprapto; Murti Astiningrum; Historiawati Historiawati (Universitas Tidar, 2018)
Research on agricultural land after the eruption of merapi aims to determine the impact of the effect of mycorrhizal and organic material to the growth and yield of onion. The experiment was conducted in greenhouse Department of Agriculture, Government of Municipality Magelang, with a factorial experiment arranged in a complete randomized block design, with two treatment factors and repeated three times. The first factor is the treatment of a mixture of organic material and mycorrhizal: cocopeat 20 t/ha+mycorrhizal (10 g/planting hole), husk charcoal 20 t/ha+mycorrhizal (10 g/planting hole) and peat 20 t/ha+mycorrhizal (10 g/planting hole). The second factor is the dose of silty soil consists of four levels: 0, 2.5, 5 and 7.5 t/ha (%). The results showed that the kind of organic material and mycorrhizal added on cocopeat, husk charcoal and peat has not been able to influence the number of leaves, number of tubers per hill, the dry weight of the top of the plant, the dry weight of the roots of plants, dried tubers per hill, and the crop growth rate, The addition of clay soil which increased 7.5% on a sand media merapi eruption is able to increase the dry weight of the top of the plant, and the crop growth rate.